Pengujian Kepatuhan Sistem Pengendalian Internal Siklus Pengeluaran Kas - Meilani Melisa Mangundap; Alfian Maase; Feri Fengki Mokalu (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
This study aims to examine the level of compliance with the implementation of the internal control system in the cash disbursement cycle. The novelty of this study lies in integrating compliance testing based on the organization’s Standard Operating Procedures (SOPs) with the Internal Control–Integrated Framework of COSO (2013). This study employed a descriptive qualitative approach. Data were collected through non-participant observation, semi-structured interviews, documentation, and vouching of budget realization transaction samples. The data were analyzed using descriptive qualitative analysis combined with a compliance test based on the Standard Operating Procedures (SOP) for Budget Determination, the SOP for Budget Realization, and the five components of the COSO (2013) Internal Control Framework. The results indicate that the segregation of duties and responsibilities, the budgeting process, and most stages of the budget realization process—including submission, approval, verification, payment, recording, preparation of accountability reports, and document archiving—have been implemented in accordance with the established Standard Operating Procedures (SOPs). The vouching test of 33 audit items showed that 26 items complied with the SOPs, 5 items were non-compliant, and 2 items were not applicable for testing, resulting in an overall compliance rate of 83.8%. The findings, it can be concluded that the internal control system for the cash disbursement cycle at Eben Haezar Foundation Manado has been well designed; however, its implementation has not yet achieved full compliance, particularly regarding the consistency of the verification sequence prior to authorization. This study are expected to serve as a reference for future research in developing studies on internal control systems, particularly by expanding the transaction samples tested, examining other aspects of internal control, and conducting comparative studies on the implementation of internal control systems in similar nonprofit organizations.